Experimental investigation of a loop heat pipe with a flat evaporator and cupric oxide nanofluids as working fluid - Tianyuan Zhao (Elsevier, 2021)
Loop heat pipe (LHP) is widely used in high-power electronic cooling as a passive cooling device. In this paper, the LHP system was designed with a flat evaporator and a capillary biporous wick with cupric oxide nanofluids as working fluid in LHP. The capillary biporous wick was sintered by nickel powder and the nanofluids were prepared by a two-step method. The startup tests, variable heat load tests, and performance degradation tests of LHP were conducted respectively and the thermal resistance was further analyzed. The results showed that, compared with distilled water, the maximum heat load increased from 290 W to 310 W and the minimum startup heat load decreased from 40 W to 20 W with nanofluids as working fluid. Both the temperature of the evaporator wall and the thermal resistance were reduced in startup tests. At the heat load of 50 W, the performance improvement was the most noticeable, where the temperature of the evaporator wall was reduced by 12.7 °C, the thermal resistance of the evaporator was reduced by 26.9%, and the thermal resistance of the LHP system was reduced by 17.6%. With a variable heat load ranging from 50 W to 290 W, the response speed of LHP became faster and the temperature fluctuation was smaller. The LHP with nanofluids as working fluid still operated normally and the change of thermal resistance with the varies of heat load had the same tendency as the previous experiment in performance degradation tests of 2 months.